Pollination of the apple tree. I. Cultivar golden delicious - Pasqual, Moacir; Petri, José Luiz; Pereira, Adilson José (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was undertaken in 1978/79, in Caçador and São Joaquim, on apple tree cv. Golden Delicious/MM-106, with the following treatments: Caçador: Golden Delicious x (Fuji, Granny Smith, Gala, Blackjon, Starkrimson, Willie Sharp, Delcon, Mollie's Delicious), free pollination, self fertility and parthenocarpy. São Joaquim: Golden Delicious x (Fuji, Gala and Hawaii). It was used a complete randomization, with four repplications and 50 flowers/plot. It was also determined the percentage of pollen germination, the number of anthers and the pollen/anthers number of grains. There was compatibility among apple tree cv. Golden Delicious and all the cultivars tested, and the best combinations were obtained with Fuji, Granny Smith, Gala and Blackjon in Caçador, and with Fuji in São Joaquim. The taxes of self-fertility and parthenocarpy were insufficient to pollen was low. The pollen conserved its germination power just for fifteen days in the ambient temperature, and for two months at - 7 °C.
Keywords: apple tree; pollination; fruit set